2021
DOI: 10.1093/sleep/zsab069
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-dependent prospective memory consolidation is impaired with aging

Abstract: Study Objectives Existing literature suggests that sleep-dependent memory consolidation is impaired in older adults but may be preserved for personally relevant information. Prospective memory (PM) involves remembering to execute future intentions in a timely manner and has behavioural importance. As previous work suggests that N3 sleep is important for PM in young adults, we investigated if the role of N3 sleep in PM consolidation would be maintained in older adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The lack of significant association could be explained by the low variability of this spindle feature. However, this result is consistent with previous studies conducted in healthy adults and revealing no significant association between sleep spindles and retrieval of intentions ( Scullin et al, 2019 ; Leong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The lack of significant association could be explained by the low variability of this spindle feature. However, this result is consistent with previous studies conducted in healthy adults and revealing no significant association between sleep spindles and retrieval of intentions ( Scullin et al, 2019 ; Leong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, these results are not consistently reported since Cunningham et al (2021) found a negative association between SWS and PM performance in young adults. In the study by Leong et al (2021), while older adults had lower PM performance and spent less time in SWS than young adults, no significant relation was found between SWS and PM in the older group. The authors suggested that the role of SWS on 10.3389/fnins.2022.908268 PM consolidation may be disrupted and thus ineffective in older adults.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…One important dimension of generalizability is how consistent the effects of sleep on emotional memory are across the life span. Aging is characterized by marked changes in sleep quality and physiology, which are implicated in changes in and deterioration of sleep-based memory consolidation ( 44 52 ). By older age, there also can be a diminution of negative memory biases and a shift toward positive memory ( 53 , 54 ), a shift that is also seen in sleep-based memory processing ( 55 ).…”
mentioning
confidence: 99%
“…Memory consolidation is presumed to be a building block of overall cognitive functioning, with cognitive functioning known to decline progressively across the adult life span to the point that independent living becomes disrupted (e.g., early stages of Alzheimer disease and related dementias). The preponderance of evidence points to memory consolidation being reduced or absent even in healthy older adults (Leong, Lo, & Chee, 2021;Jones, Mackay, Mantua, Schultz, & Spencer, 2018;Gui et al, 2017). However, researchers are still determining the psychological and neurobiological mechanisms by which memory consolidation declines with aging (Scullin & Gao, 2018;Mander, Winer, & Walker, 2017).…”
Section: Introductionmentioning
confidence: 99%